A Strategi Pembelajaran dan Evaluasi dalam Pengembangan Kemampuan Menulis Siswa SMA - -, Aviva Octavia; Riyanti , Asih; Fajri, Dhita Nur; Rahmatang; Muharam, Indra (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This study emphasizes the significance of learning and evaluation processes in enhancing students' writing skills at the senior high school level. Learning is viewed as an interactive system between teachers and students, supported by continuous practice and exercises. Techniques such as idea development and mind mapping are employed by teachers to facilitate effective planning of writing tasks. Various assessment methods, including group assignments, individual tasks, and formative evaluations, are utilized to comprehensively measure students' writing abilities. Conducted at SMA N 5 Tarakan through interviews, the research reveals teachers' strategies in overcoming students' difficulties and monitoring their progress. The findings suggest that the application of idea development techniques and diverse evaluation approaches can significantly improve students' writing skills.